1996
DOI: 10.21273/hortsci.31.4.632d
|View full text |Cite
|
Sign up to set email alerts
|

Priming and Accelerated Aging Affect L-isoaspartyl Methyltransferase Activity in Tomato Seed

Abstract: Damage and degradation of cellular proteins is observed during seed deterioration due to aging. L-isoaspartyl methyltransferase (EC 2.1.1.77) is an enzyme hypothesized to play a role in limiting and repairing aging-induced damage of proteins. Tomato seeds (Lycopersicon esculentum `New Yorker') were assayed for changes in L-isoaspartyl methyltransferase activity during accelerated aging and after osmotic priming. Accelerated aging of seeds for 1 to 4 days at 45°C and 100% humi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
7

Year Published

1999
1999
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 0 publications
1
4
0
7
Order By: Relevance
“…For example, high concentrations of PEG inhibited the germination of Lycopersicon esculentum Mill., Avena sativa L., Castanea mollissima Blume, and Betula luminifera H.J.P.Winkl. seeds (Kester et al 1997;Xia et al 2016). This was consistent with the inhibitory effect of 25% PEG priming on the germination of H. bodinieri seeds, although such effect by PEG treatment after 6 days of storage was very weak (Fig.…”
Section: Germination Of Ultra-dry Stored Seed Requires Seed Primingsupporting
confidence: 85%
“…For example, high concentrations of PEG inhibited the germination of Lycopersicon esculentum Mill., Avena sativa L., Castanea mollissima Blume, and Betula luminifera H.J.P.Winkl. seeds (Kester et al 1997;Xia et al 2016). This was consistent with the inhibitory effect of 25% PEG priming on the germination of H. bodinieri seeds, although such effect by PEG treatment after 6 days of storage was very weak (Fig.…”
Section: Germination Of Ultra-dry Stored Seed Requires Seed Primingsupporting
confidence: 85%
“…Seed aging causes deterioration and viability loss through various biochemical changes (Kerter et al 1997;Spano et al 2006). The differences among the weed species in the rate of decline in viability could be attributed to inherent genetic and physiological characteristics and their interactions with the physical environment.…”
Section: Resultsmentioning
confidence: 99%
“…In naturally-aged barley seeds the activity of the enzyme declined and the level of 'unrepaired' L-isoaspartyl residues increased as viability declined. Similarly, Kester et al (1997) showed that the activity of L-isoaspartyl methyltransferase decreased in artificially aged tomato seeds as germination rate and viability declined. The studies of Osborne and her group also demonstrate that repair is an essential element contributing to survival of dehydrated orthodox seeds.…”
Section: The Presence and Operation Of Repair Mechanisms During Rehydmentioning
confidence: 97%